Pengaruh Kualitas Pelayanan dan Kualitas Produk terhadap Volume Penjualan pada PT. Duamitra Oil - Sari, Ayu Dita; Icmi, Arida Nur; Tahanudin, Tahanudin (BUDGETING : Journal of Business, Management and Accounting, 2026)
This research aims to examine the influence of service quality and product quality on sales volume at PT. Duamitra Oil. This research was carried out using a quantitative approach using a survey method with a research instrument in the form of a questionnaire. Sampling was carried out on 36 respondents who were regular customers. Data quality testing in this research was carried out through validity testing, reliability testing and classical assumption testing, while hypothesis testing was carried out through multiple regression analysis and t test. Partially, Service Quality has a significant effect on sales volume at PT. Duamitra Oil. Partially, product quality has a significant effect on sales volume at PT. Duamitra Oil. Simultaneously, service quality and product quality have a significant effect on sales volume at PT. Duamitra Oil.   Keywords: Product Quality, Sales Volume, Service Quality,